2015
DOI: 10.1056/nejmoa1506348
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD38 with Daratumumab Monotherapy in Multiple Myeloma

Abstract: BACKGROUNDMultiple myeloma cells uniformly overexpress CD38. We studied daratumumab, a CD38-targeting, human IgG1κ monoclonal antibody, in a phase 1-2 trial involving patients with relapsed myeloma or relapsed myeloma that was refractory to two or more prior lines of therapy. METHODSIn part 1, the dose-escalation phase, we administered daratumumab at doses of 0.005 to 24 mg per kilogram of body weight. In part 2, the dose-expansion phase, 30 patients received 8 mg per kilogram of daratumumab and 42 received 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
814
2
25

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 989 publications
(899 citation statements)
references
References 24 publications
25
814
2
25
Order By: Relevance
“…The anti-CD38 monoclonal antibody daratumumab has shown a favorable safety profile and encouraging efficacy in patients with refractory multiple myeloma (25)(26)(27), and the anti-CD38 SAR650984 is being examined as a treatment for CD38 ϩ hematological malignancies, including AML (clinicaltrials.gov registration NCT01084252). Here, we have found that treatment of AML cell lines and primary AML apheresis samples with IFN␥ leads to the up-regulation of M1-related markers and of the daratumumab target CD38.…”
mentioning
confidence: 99%
“…The anti-CD38 monoclonal antibody daratumumab has shown a favorable safety profile and encouraging efficacy in patients with refractory multiple myeloma (25)(26)(27), and the anti-CD38 SAR650984 is being examined as a treatment for CD38 ϩ hematological malignancies, including AML (clinicaltrials.gov registration NCT01084252). Here, we have found that treatment of AML cell lines and primary AML apheresis samples with IFN␥ leads to the up-regulation of M1-related markers and of the daratumumab target CD38.…”
mentioning
confidence: 99%
“…9 Other new promising immune therapies include anti-PD1 agents, vaccines and CAR T-cell approaches in MM and monoclonal Abs against CD38. 8,[53][54][55][56] Abbreviations: Auto-HCT = autogeneic hematopoietic cell transplantation; CIBMTR = Center for International Blood and Marrow Transplant Research; m = months; NRM = non-relapse mortality; NS = not stated; OS = overall survival; RIC = reduced-intensity conditioning; RR = relapse rate; yrs = years.…”
Section: Immunomodulationmentioning
confidence: 99%
“…A phase I trial of elotuzumab in combination with bortezomib induced responses in 48% of patients with relapsed/refractory myeloma . The anti-CD38 daratumumab looks promising in phase I/II trials (Plesner et al, 2014;Moreau et al, 2014;Lokhorst et al, 2015), and three phase III trials of daratumumab plus various chemotherapy regimens are currently recruiting in newly diagnosed and relapsed populations. The antibody-drug conjugates lorvotuzumab mertansine (with lenalidomide/dexamethasone, ORR 59%) (Berdeja et al, 2012) and indatuximab ravanstine (with lenalidomide/dexamethasone, ORR 78%) (Kelly et al, 2014); and the AKT inhibitor afuresertib (with bortezomib/dexamethasone, ORR 49%) (Voorhees et al, 2013) demonstrate activity in phase I trials in relapsed/refractory patients.…”
Section: New Agentsmentioning
confidence: 99%
“…Monoclonal antibodies are not particularly myelosuppressive: elotuzumab has lower neutropenia rates than the control group (Lonial et al, 2015), and although a minority of patients receiving daratumumab developed low cell counts this was not dose-dependent (Lokhorst et al, 2015). Given this low toxicity they are attractive targeted therapies for use in consolidation and maintenance phases, to inhibit residual myeloma clones.…”
Section: New Agentsmentioning
confidence: 99%